An improved predictor–corrector entry guidance method for hypersonic flight vehicle. (October 2017) - Fu, Wenxing; Liu, Dakai; Chen, Kang; Yan, Binbin
This article improves an enhanced predictor–corrector entry guidance method for hypersonic flight vehicle. To compensate for the shortcoming that the enhanced predictor–corrector guidance method sacrifices guidance precision to meet path constraints, this article develops an improved predictor–corrector guidance method. Through consuming more energy in the middle section of entry, the guidance method greatly reduces the load in the end section of entry, earning more time for the guidance bank angle which aims at ensuring entry precision to function in the end section, and thus, the entry precision is improved. The simulation results on the CAV-H flight vehicle show preliminarily that the guidance method effectively enhances the guidance precision for both orbital and suborbital entry missions and strictly constrains distance errors within the stipulated range. Furthermore, this method is also fairly effective for flight vehicles with lower lift-to-drag ratio (X-33). Then, the flight vehicle with a higher lift-to-drag ratio is chosen as the simulation target to further examine the guidance method's effectiveness and precision.